2022
DOI: 10.3390/agriculture12121988
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pulsed, Scanning and Constant (16- and 24-h) Modes of LED Irradiation on the Physiological, Biochemical and Morphometric Parameters of Lettuce Plants (Lactuca sativa L.) while Cultivated in Vertical Farms

Abstract: In city farming, when growing green crops, a significant part of the production cost is the cost of electricity for lighting. The physiology, biochemistry, morphology and productivity of plants can be affected by changing irradiation modes and these changes reduce electricity costs. However, the results of studies in the literature are contradictory. In this work, we investigated the effect of impulse (frequency 1000 Hz and duty cycle 67%), scanning (the principle of running lights) and constant 16 h and 24 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…In turn, LEF suppression can result from the decreasing of the fraction of the actinic light absorbed by the leaf and fraction of the absorbed light distributed to photosystem II ( Figure 4 ), which are caused by lowering content of chlorophylls ( Figure 5 and Figure 6 ). This potential mechanism ( Figure 10 ) is in a good accordance with the decreasing content of chlorophylls in lettuce plants under the short photoperiod, which is shown in a number of works [ 28 , 30 , 39 ]; however, it should be noted that changes in the chlorophyll content are not shown in several works [ 29 , 40 ]. Increasing the chlorophyll content under the increased photoperiod can be caused by the direct light influence on the reduction of protochlorophyllide to chlorophyllide [ 41 , 42 ]; this hypothesis is in accordance with the negative influence of the increased photoperiod on the chlorophyll content under the constant total light integral for one day [ 30 ].…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…In turn, LEF suppression can result from the decreasing of the fraction of the actinic light absorbed by the leaf and fraction of the absorbed light distributed to photosystem II ( Figure 4 ), which are caused by lowering content of chlorophylls ( Figure 5 and Figure 6 ). This potential mechanism ( Figure 10 ) is in a good accordance with the decreasing content of chlorophylls in lettuce plants under the short photoperiod, which is shown in a number of works [ 28 , 30 , 39 ]; however, it should be noted that changes in the chlorophyll content are not shown in several works [ 29 , 40 ]. Increasing the chlorophyll content under the increased photoperiod can be caused by the direct light influence on the reduction of protochlorophyllide to chlorophyllide [ 41 , 42 ]; this hypothesis is in accordance with the negative influence of the increased photoperiod on the chlorophyll content under the constant total light integral for one day [ 30 ].…”
Section: Discussionsupporting
confidence: 78%
“…It can be expected that increasing the photoperiod should additionally increase the lettuce production; however, the literature results seem to be contradictory. Work [ 29 ] shows that the increased photoperiod does not significantly change the lettuce production, and can even, decrease the linear electron flow; in contrast, some studies [ 28 , 30 ] reported a positive influence of the increased photoperiod on the photosynthetic parameters and production of lettuce plants. In this work we investigated the effect of photoperiod on the photosynthetic parameters, respiration, content of chlorophylls, biomass, and dry weight.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations